Knowledge of Saudi dental students and interns towards luting cements and their applications in fixed prosthodontics - Passent Ellakany; Reem Abualsaud; Mohammed M. Gad; Sara Atteya; Omar A. El Meligy; Osama A. Qutub; Amr A. Mahrous (BMC, 2023)
Abstract Background Enhancement of students' knowledge is essential in improving their clinical skills and performance. Thus, the curriculum should be prepared to achieve a better outcome. The current study aimed to determine the dental students' and interns' basic knowledge towards dental luting cements and their application in dental practice to improve the theoretical and clinical training sections. Materials and methods A cross-sectional study was conducted among dental students and interns at three Colleges of Dentistry in the Kingdom of Saudi Arabia between September 2019-June 2020. An online questionnaire was used which included demographic data, questions about luting cement usage, cementation techniques, and commonly used cements in dental clinics. Descriptive analysis and chi-square test were used to show the association between level of dental education and the use of dental cements using SPSS software. The significance level was set at 5%. Results The total respondents were 626 dental students/interns of whom 78.8% were undergraduate dental students. Participants who reported undergraduate studies as the source of information were 79.7%. The type of restoration was the main factor in luting cement selection (62.6%). Concerning the isolation technique in cementing laminate veneers, 49.7% used dri-angles, cotton rolls and saliva ejectors. Dual-cure resin cement was the most common cement used in all the mentioned restorations except in pressed porcelain laminate veneers and cement-retained implant-supported restorations. Conclusions Students' knowledge and practice in managing dental implants and porcelain laminate veneers need to be improved. The selection of a luting agent for a given restoration by students and interns was based on the basic knowledge, available cement, and the type of restoration. Awareness towards the management of short prepared teeth and custom-made cast posts and cores is also limited.